Biology and natural history of Caladenia - Dixon, Kingsley; Tremblay, R. (CSIRO Publishing, 2009)
The genus Caladenia comprises species that exhibit remarkable consistency in terms of growth form and phenological patterns. All taxa are herbaceous perennials, with the shoot arising annually from a single, usually spheroid, tuber and producing a single, hairy leaf. The tuber is annually replaced either side-by-side with the parent tuber or terminating a descending structure known as a dropper. The dropper is a depth-seeking mechanism that enables placement of the tuber at depth in the soil as a means to avoid predation by surface-foraging native mammals or away from the high temperatures and desiccating conditions during summer dormancy. The 3 - 5 attenuated roots produced at the junction between the tuber and shoot and produced late in the growing cycle and devoid of mycorrhiza suggest their functional significance may relate to water uptake. Mycorrhizal endophytes are confined to a hypertrophic stem region at the soil surface (collar) subtending the leaf that positions the collar directly in the organically rich zone at the soil surface. This morphology is a unique characteristic of several Australasian orchids in the tribe Diuridae. Mycorrhizal infection occurs rapidly, with maximum colonisation in concert with the onset of breaking rains. Pelotons are restricted to cortical cells, with fully developed pelotons throughout infected tissues within a week or so of soil wetting. Infection occurs as a 'once-off' event, with little evidence of secondary infection later in the growth cycle and no evidence of peloton digestion. Some taxa utilise vegetative propagation, often leading to localised clustering as for taxa in the 'filamentosa' complex or, extensive clonal mats as found in Caladenia flava and C. latifolia where daughter tubers are produced at the end of extending horizontal outgrowths. For the majority of taxa, plants remain dry-season (summer) dormant from a few months up to 7 months for arid-zone taxa, with shoot emergence from the tuber of temperate species thought to occur in response to a drop in the mean minimum temperature. Pollination biology of Caladenia is apparently through a process of deception, either as food or sexual mimics, with some taxa engaging in self-pollination. Here we review the natural history of Caladenia and acknowledge that much of our understanding is based on assumptions of the biology of terrestrial orchids in general and emphasise areas of research and biological enquiry that will be critical in the development of an effective conservation program for the genus. © CSIRO 2009.